Genetic variability and correlation analysis among grain yield and early seedling vigour in rice (Bangladesh Journal of Botany, 2025)
In the present study, 42 rice genotypes were evaluated for genetic variability, heritability, and trait associations for 13 traits to enhance resilience in direct-seeded conditions. Significant variation (ANOVA) was observed, with the widest range in seedling vigour index-I (1533.1-3708.8) and the narrowest in root-to-shoot ratio (1.13-2.55). High genotypic (GCV) and phenotypic (PCV) coefficients of variation, along with high heritability and genetic advance, were recorded for seedling vigour index-II (GCV: 25.06; PCV: 25.87), grain yield/plant (24.59; 25.39), germination index, seedling dry weight, shoot length, and root-to-shoot ratio, indicating strong genetic control and potential for phenotypic selection. Seedling vigour index-II (SVI-II) showed strong positive correlations with shoot dry weight (0.97**), shoot fresh weight (0.87**), and shoot height (0.95**), suggesting indirect selection of these traits could improve early vigour and yield in direct-seeded rice. The findings highlight traits with high heritability and genetic potential for breeding resilient genotypes.Bangladesh J. Bot. 54(4): 1027-1033, 2025 (December)